Fuzzy control based virtual synchronous generator for self-adaptative control in hybrid microgrid - Lyu, Ling (2023)
Maintaining the stability of low-inertia microgrid becomes a key challenge in the presence of high penetration of renewable energy sources. However, in such systems, the virtual inertia values are often fixed constants, and the choice of their values will significantly affect the frequency and voltage stability of the microgrid. Higher frequency and voltage oscillations may occur due to improper selection of fixed virtual inertia values. Therefore, virtual inertia-based control has attracted a lot of attention. In this paper, an adaptive virtual inertia control system using a fuzzy system is proposed by setting fuzzy logic rules and affiliation functions to provide adaptive inertia control for the system to ensure the frequency and voltage stability. In the proposed adaptive control strategy, the virtual inertia values are automatically adjusted according to the signal deviation and rate of change of the actual system, avoiding the selection of inappropriate inertia values and providing fast inertial response. Simulation and experimental results show that the proposed adaptive control algorithm, by combining the advantages of large inertia and small inertia, enables effective improvement of the dynamic response of the system voltage and frequency in both rectifier and inverter modes. The effectiveness of the proposed control strategy is verified.